2019
DOI: 10.21608/eajbsf.2019.41514
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Biochemical Effects of Lufenuron and Rice Bran on Desert Locust, Schistocerca gregaria (Forskal) (Orthoptera: Acrididae)

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Numerous studies have proven the activity of lufenuron (CSI) as an inhibitor of ovicidal, transovarial-ovicidal, and embryonic development of pests at the recommended dose (Fonseca et al, 2015 andSampson et al, 2017). Also, it causes different morphological, biochemical, and histological malformation in different stages of the desert locust (Abdel Rahman, 2017;Al-Zeeb et al, 2018;Mahdy et al, 2019& 2020and Said, 2020. As well it has reasonable persistence and low toxicity against non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have proven the activity of lufenuron (CSI) as an inhibitor of ovicidal, transovarial-ovicidal, and embryonic development of pests at the recommended dose (Fonseca et al, 2015 andSampson et al, 2017). Also, it causes different morphological, biochemical, and histological malformation in different stages of the desert locust (Abdel Rahman, 2017;Al-Zeeb et al, 2018;Mahdy et al, 2019& 2020and Said, 2020. As well it has reasonable persistence and low toxicity against non-target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Botanical insecticides such as agricultural waste products and plant extracts degrade quickly in air and moisture by detoxification enzymes; this refers to less environmental persistence and lower dangers to organisms that aren't the target (Isman, 2008). Rice bran extract is one of the agricultural waste products that showed a serious effect on the desert locust S. gregaria life cycle (Mahdy et al, 2019(Mahdy et al, & 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This study's findings exhibit consistency with recent findings illustrating the impact of crude extracts or essential oils of botanical origin in terms of damaging the mid‐gut of different economically challenging pests (Mahdy et al . 2023; Muthu et al . 2023; Ngegba et al .…”
Section: Discussionmentioning
confidence: 99%
“…BPUs are known to be effective against insect and tetranychid mite pests [28]. Mahdy et al found that the percentages of fifth nymphal instars of the desert locust Schistocerca gregaria treated with different concentrations of lufenuron failed to ecdysis to adults significantly increased compared with the control [21]. After D. citri nymphs were exposed to diflubenzuron for 48 h, the cumulative mortality sharply increased [27].…”
Section: Discussionmentioning
confidence: 99%
“…Merzendorfer reported that triflumuron was a benzoylphenylurea which could lead to molting failure, deformity and even death of pests by interfering with the entomic chitin biosynthesis pathway [1]. Mahdy et al found that the treatment with different concentrations of lufenuron (CSIs) against the fifth nymphal instar females of the desert locust Schistocerca gregaria resulted in the failure of ecdysis to adults [21]. Diflubenzuron (DFB), a kind of benzoylphenylurea-selective insecticide with low toxicity, interferes with chitin formation in the procuticle and the deposition of epicuticle, resulting in abortive molting and other alterations in the physiological processes of various arthropod species.…”
Section: Introductionmentioning
confidence: 99%